Analysis of the training of undergraduate students and the influence on clinical aspects and lifestyle (International Seven Journal of Health Research, 2024)
The aim of this study was to investigate whether the training obtained during undergraduate courses in Administration, Agronomic Engineering, Physiotherapy, Law, Nutrition, Physical Education and Biology influences the general clinical aspects and quality of life of students. This was an exploratory study with a qualitative-quantitative approach through a bibliographic review with a bibliometric approach and an online self-completion questionnaire, addressing the different subjects related to the theme of the work. The aim of this study is to propose actions that can improve students' quality of life through guidance on practicing physical activity and eating properly, as well as guidance and help with emotions in order to provide a better understanding of reality, so that they can act in a more critical and relevant way with regard to nutrition, demonstrating the need to raise awareness through education and improve quality of life regardless of the area of training, so that they can actually face the challenges during their professional journey.